1998
DOI: 10.1063/1.121627
|View full text |Cite
|
Sign up to set email alerts
|

Metal–oxide bilayer Raman scattering in SrTiO3 thin films

Abstract: We have used a metal-oxide bilayer Raman scattering technique to study lattice dynamics in SrTiO 3 thin films. The SrTiO 3 thin films were epitaxially grown on a conducting metal-oxide layer which reflects the exciting laser beam so that it does not enter the LaAlO 3 substrate. Raman scattering from the SrTiO 3 thin films was clearly observed, including the first-order Raman peaks forbidden by the cubic symmetry in single crystals. We suggest that strain exists in the films, which changes the crystal symmetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 17 publications
6
32
0
Order By: Relevance
“…The soft modes have also been seen in the case of uniaxial stress-induced [11] and hydrostatic pressure-induced [12] ferroelectricity and using far-IR spectroscopy [13], neutron scattering [14], and hyper-Raman scattering [15]. In our previous studies of STO thin films grown on LaAlO 3 substrates we observed first order Raman scattering by hard-mode TO 2 and TO 4 phonons, while the soft TO 1 mode has not been detected [16,17]. In this paper, we describe Raman scattering experiments in STO thin films grown on STO substrates with a SrRuO 3 (SRO) buffer layer in which application of an electric field allowed detailed investigation of the soft modes.…”
mentioning
confidence: 75%
“…The soft modes have also been seen in the case of uniaxial stress-induced [11] and hydrostatic pressure-induced [12] ferroelectricity and using far-IR spectroscopy [13], neutron scattering [14], and hyper-Raman scattering [15]. In our previous studies of STO thin films grown on LaAlO 3 substrates we observed first order Raman scattering by hard-mode TO 2 and TO 4 phonons, while the soft TO 1 mode has not been detected [16,17]. In this paper, we describe Raman scattering experiments in STO thin films grown on STO substrates with a SrRuO 3 (SRO) buffer layer in which application of an electric field allowed detailed investigation of the soft modes.…”
mentioning
confidence: 75%
“…Currently, potential candidates such as Ba 1 x Sr x TiO 3 (BST) for room temperature and SrTiO 3 (STO) for cryogenic temperatures are preferred because of their high dielectric constants (ε r ), good thermal stability and high frequency characteristics or nonlinear polarizability and hence should be favored for dielectric tuning as reported by Devonshire almost half a century ago. 4 The properties of almost all materials in general and ferroelectrics in particular in thin-film form differ from those of their bulk counterparts. 5 STO thin films have therefore been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Raman spectroscopy permitted to observe differences be- tween the pellet and the collected aerosols (as shown in Figure 8): the former showed the typical broad bands of the SrTiO 3 crystal (as reported in [26] at ca. 200-500 and 600-750 cm −1 ), while the latter showed bands related to first-order vibrations (broad bands at ca.…”
Section: Srtiomentioning
confidence: 99%